Pallister-Killian syndrome: Cytogenetics and molecular investigations of mosaic tetrasomy 12p in prenatal chorionic villus and in amniocytes. Strategy of prenatal diagnosis - Francesco Libotte; Domenico Bizzoco; Ivan Gabrielli; Alvaro Mesoraca; Pietro Cignini; Salvatore Giovanni Vitale; Ilaria Marilli; Ferdinando Antonio Gulino; Agnese Maria Chiara Rapisarda; Claudio Giorlandino (Elsevier, 2016)
Objective: Pallister-Killian syndrome (PKS) is a rare, sporadic genetic disorder caused by mosaic tetrasomy of the short arm of chromosome 12 (12p). Clinically, PKS is characterized by several systemic abnormalities, such as intellectual impairment, hearing loss, epilepsy, hypotonia, craniofacial dysmorphism, pigmentary skin anomalies, epilepsy, and a variety of congenital malformations. Prenatally, PKS can be suspected in the presence of ultrasound anomalies: diaphragmatic hernia, rhizomelic micromelia, hydrops fetalis, fetal overweight, ventriculomegaly in the central nervous system, congenital heart defects, or absent visualization of the stomach. In all these cases, a detailed genetic study is required. PKS is diagnosed by prenatal genetic analysis through chorionic villus sampling, genetic amniocentesis, and cordocentesis. Case Report: We report two cases of PKS with prenatal diagnosis of isochromosome 12p made by cytogenetic studies. The first case is of a 36-year-old pregnant woman who underwent genetic chorionic villus sampling at 13th weeks of gestation after 1st trimester prenatal ultrasound revealed clinical features of PKS: flat nasal bridge and fetal hydrops. The second case is of a 32-year-old pregnant woman with genetic amniocentesis at 17th weeks of gestation that showed mos46,XX[21]/47,XX,+i(12p) associated to PKS. Conclusion: New molecular cytogenetic techniques array comparative genomic hybridization and fluorescence in-situ hybridization in association with conventional karyotype are pivotal innovative tools to search for chromosomic anomalies and for a complete prenatal diagnosis, especially in cases such as PKS where array comparative genomic hybridization analysis alone could not show mosaicism of i(12p).